Slavery in Africa - Rathbone, Richard (My University, 1979)
The almost casual concern of African specialists with a question of such significance as the social consequences of the slave trade on African societies appears at first sight rather surprising. While this problem is the object of some judgement or other in most regional or general treatments of African history that extend to the period of the trade, it has attracted far less attention in the monographic literature. Even more surprising is the fact that despite the wide range of historical assessments made by various scholars, there has been little direct confrontation of opposing views. The brief - and generally inconclusive - exchanges between Walter Rodney (1966) and John Fage (1959;1969;1975) and between Fage and Wrigley (1971) seem rather to underline this observation than to contradict it. Whatever the sources of this lacuna might be, they are certainly fed by the generally speculative way in which the issue has been pursued and, more seriously, the absence of any sound theoretical framework within which the weighing of evidence and testing of hypotheses can proceed. In this paper I propose to examine the principal contributions to this discussion with a view to assessing how the debate on this important question could be most fruitfully pursued, and to raise a few suggestions with regard to the strengthening of the theoretical foundations of the debate.
African Studies Seminar series. Paper presented June 1979
Keywords: Slavery. Africa; Slave trade. Africa